Renormalization group flow of the standard model's coupling constants - Hong, Xing Ru (2018)
This thesis will provide a discussion on the renormalization for the phi-4 theory as an introduction to renormalization groups (RGs) and renormalization group equations (RGEs). The Gell-Mann-Low equation will be introduced. The relationship between the Gell-Mann-Low equation and the gauge coupling constants will be explained. As this thesis is focused on the renormalization group flow, the general gauge coupling constants for the abelian U(1) gauge group and the non-abelian SU(N) gauge group will be examined. The renormalization group flow for the coupling constants of the Standard Model (SM) and the Minimal Supersymmetric Standard Model (MSSM) will be discussed eventually, together with some details on these models and its consequences.